Nephronectin Is Required for Vascularization in Zebrafish and Sufficient to Promote Mammalian Vessel‐Like Structures in Hydrogels for Tissue Engineering - Chinmoy Patra; Amey Rayrikar; Ganesh Wagh; Florian Kleefeldt; Kaveh Roshanbinfar; Florian Cop; Iva Nikolic; Mirko H. H. Schmidt; Amparo Acker‐Palmer; Süleyman Ergün; Felix B. Engel (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Organs and tissues need to be vascularized during development. Similarly, vascularization is required to engineer thick tissues. How vessels are formed during organogenesis is not fully understood, and vascularization of engineered tissues remains a significant challenge. Methods and Results Here, we show that the extracellular matrix protein nephronectin is required for vascularization during zebrafish development as well as adult fin regeneration and is sufficient to promote mammalian vessel formation and maturation. Nephronectin a morphants and mutants exhibit diminished axial vein sprouting and posterior intersegmental vessel growth. Notably, the angiogenesis‐associated integrins itgav and itgb3.1 are coexpressed with nephronectin a in the region of the caudal vein plexus and posterior somites; nephronectin binds to integrin alpha‐V/integrin beta‐3.1 (ITGAV/ITGB3.1), and itgav morphants phenocopy nephronectin a mutants. In addition, nephronectin a mutants showed decreased vessel maturation compared with wild‐type siblings during caudal fin regeneration in adult zebrafish. Moreover, nephronectin promotes mammalian endothelial cell migration and tube formation in 2D and 3‐dimensional in vitro tissue culture. Further, nephronectin enhances vascular endothelial growth factor‐induced periaortic vascular capillary interconnectivity, vessel diameter, and vessel stability. Conclusions Collectively, our results identify nephronectin as a proangiogenic factor during embryonic development, which can be used to improve the vascularization of engineered tissues.